Modernising vocational education and training : fourth report on vocational training research in Europe: background report. Volume 3 - Descy, Pascaline [Mitarbeiter]; Tchibozo, Guy [Mitarbeiter]; Tessaring, Manfred [Mitarbeiter]; Lasonen, Johanna [Mitarbeiter]; Gordon, Jean [Mitarbeiter]; Dauty, Francoise [Mitarbeiter]; Kirsch, Jean-Louis [Mitarbeiter]; Lemistre, Philippe [Mitarbeiter]; Coles, Mike [Mitarbeiter]; Werquin, Patrick [Mitarbeiter]; Bohlinger, Sandra [Mitarbeiter]; Münk, Dieter [Mitarbeiter] (Publications Office of the European Union, 2009)
"The fourth report on VET research documents, discusses and analyses the socioeconomic context and VET reforms, based on latest research evidence. The background report collects contributions from renowned experts and researchers. Contributions have been regrouped into three separate volumes. This volume addresses various aspects and dimensions of the VET reform process such as: the development of national qualification systems ands frameworks, policies to improve the attractiveness of VET and European level tools and strategies, such as the European qualification framework." (Herausgeber, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 2 Trends & Entwicklungen; S 2.3 Berufsbildungspolitik; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; T 3.5 Statistik; G 2.1 Globalisierung; I 2.2 Europa; Berufsbildung; Modernisierung; Reform; Bildungsmarketing; EU-Bildungspolitik; Qualifikation; Beziehung Bildungssystem Beschäftigungssystem; Anrechnung von Bildungsleistungen; Europäischer Qualifikationsrahmen; Europäisches Leistungspunktesystem; Berufsbildungsstatistik; Wettbewerbsfähigkeit; Indikatoren; Europa